The Association of Circulating CD14++CD16+ Monocytes, Natural Killer Cells and Regulatory T Cells Subpopulations With Phenotypes of Cardiovascular Disease in a Cohort of Peritoneal Dialysis Patients - Duni, Anila; Vartholomatos, Georgios; Balafa, Olga; Ikonomou, Margarita; Tseke, Paraskevi; Lakkas, Lampros; Rapsomanikis, Karolos Paulos; Kitsos, Athanasios; Theodorou, Ioanna; Pappas, Charalambos; Naka, Katerina K.; Mitsis, Michael; et al. (Frontiers in Medicine, 2021)
The altered expression of immune cells including monocyte subsets, natural killer (NK) cells and CD4+CD25+ regulatory T cells (Tregs) in end-stage kidney disease, affect the modulation of inflammation and immunity with significant clinical implications. The aim of this study was to investigate the profile of specific immune cells subpopulations and their correlations with phenotypes of established cardiovascular disease (CVD), including coronary artery disease (CAD) and heart failure (HF) in peritoneal dialysis (PD) patients. Materials and Methods: 29 stable PD patients and 13 healthy volunteers were enrolled. Demographic, laboratory, bioimpedance measurements, lung ultrasound and echocardiography data were collected. The peripheral blood immune cell subsets analysis was performed using flow cytometry. Results: PD patients compared to normal controls had lower total lymphocytes (22.3 ± 6.28 vs. 31.3 ± 5.54%, p = <0.001) and B-lymphocytes (6.39 ± 3.75 vs. 9.72 ± 3.63%, p = 0.01) as well as higher CD14++CD16+ monocytes numbers (9.28 ± 6.36 vs. 4.75 ± 2.75%, p = 0.0002). PD patients with prevalent CAD had NK cells levels elevated above median values (85.7 vs. 40.9%, p = 0.04) and lower B cells counts (3.85 ± 2.46 vs. 7.2 ± 3.77%, p = 0.03). Patients with increased NK cells (>15.4%) had 3.8 times higher risk of CAD comparing with patients with lower NK cell levels (95% CI, 1.86 – 77.87; p = 0.034). B cells were inversely associated with the presence of CAD (increase of B-lymphocyte by 1% was associated with 30% less risk for presence of CAD (95% CI, −0.71 – 0.01; p = 0.05). Overhydrated patients had lower lymphocytes counts (18.3 ± 4.29% vs. 24.7 ± 6.18%, p = 0.006) and increased NK cells [20.5% (14.3, 23.6) vs. 13.21% (6.23, 19.2), p = 0.04)]. In multiple logistic regression analysis the CRP (OR 1.43; 95% CI, 1.00 – 2.05; p = 0.04)] and lymphocytes counts (OR 0.79; 95% CI, 0.63–0.99; p = 0.04)] were associated with the presence of lung comets. Patients with higher NK cells (>15.4%, n = 15) were more likely to be rapid transporters (D/P creatinine 0.76 ± 0.1 vs. 0.69 ± 0.08, p = 0.04). Patients displaying higher Tregs (>1.79%) were older (70.8 ± 10.7 years vs. 57.7 ± 14.7years, p = 0.011) and had higher nPCR (0.83 ± 0.14 vs. 0.91 ± 0.17, p = 0.09). Conclusion: Future research is required to evaluate the role of immune cells subsets as potential tools to identify patients at the highest risk for complications and guide interventions.